(untitled) (Revista "Boletín el Conuco", 2020)
Planning of urban public transport as part of government plans of the candidates for mayor of Villavicencio. In recent years the city has had an important growth driver (the road network has been modified with the construction of new roads) that has a development perspective . However , this growth has come at the expense in terms of the strategies presented in the government’s plans do not meet the purpose of efficiency and effectiveness. As proposed methodology is to perform an evaluation sheet to analyze performance indicators strategies to improve urban transport service within government plansin the last three administrations and as a result it is to assess the efficiency and effectiveness of service considering that this is an important economic resource for the region and represents an important service to improve the welfare of the community.